Hyperopic reserve as a predictor of myopia incidence in schoolchildren aged 6–12 years: a 24-month prospective cohort study - Dong, Wei; Fu, Kunlin; Zhang, Ye; Li, Yangbing; Liu, Chengfei; Wang, Zihao; Li, Yanying; Song, Boyang; Du, Zhaojiang (Frontiers in Public Health, 2025)
PurposeTo investigate the age-specific prevalence of hyperopic reserve deficiency and its predictive value for incident myopia among 6-12-year-old schoolchildren in Xi’an, China.MethodsThis prospective cohort study enrolled 15,046 students from 30 primary schools. Diopter and visual acuity were assessed at baseline (2021) and follow-up (2023). Hyperopic reserve thresholds followed Chinese national guidelines (SE: <+1.00D for ages 6–8, <+0.50D for age 10). Multivariable logistic regression identified risk factors for myopia progression.ResultsMyopia prevalence increased significantly with age (10.25% at 6 years to 49.77% at 12 years; p < 0.001). Females exhibited higher overall myopia rates (26.38% vs. 21.26%; p < 0.001). Hyperopic reserve deficiency peaked at age 8 (91.62%) and declined thereafter. Children with baseline reserve −0.5D to 0D demonstrated a 40.27% myopia conversion rate, compared to 3.33% in those with > + 2.00D (p < 0.001). Key risk factors included parental myopia (OR = 1.60, 95% CI:1.42–1.80, p < 0.001 for maternal, OR = 1.35, 95% CI:1.20–1.54, p < 0.001 for paternal), prolonged study time (OR = 1.49 95% CI: 1.33–1.68, p < 0.001), prolonged screen time (OR = 1.17, 95% CI:1.04–1.30, p = 0.007), and high sugar intake (OR = 1.46, 95% CI:1.30–1.64, p < 0.001), while outdoor activity (OR = 0.47, 95% CI:0.40–0.55, p < 0.001), adequate sleep (OR = 0.84, 95% CI:0.75–0.95, p = 0.004) and good learning posture were protective(OR = 0.63, 95% CI:0.56–0.71, p<0.001).ConclusionHyperopic reserve −0.5D to 0D identifies high-risk subgroups for myopia development, particularly among females. Preventive interventions targeting reserve preservation should commence by age 6, integrating school-based strategies and personalized clinical protocols.